2021
DOI: 10.1001/jamanetworkopen.2021.32138
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Clinician Perspectives on Challenging Parent-Clinician Relationships in Pediatric Oncology

Abstract: This survey study investigates the prevalence of challenging parent-clinician relationships in pediatric oncology and factors associated with these challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…[21][22][23] Our previous work found that not all parents of children with cancer experienced supportive relationships with their children's oncology clinicians, with nearly one-quarter of these parents identifying substantial challenges soon after diagnosis. 9 Such relationships can evolve; however, in the best case, a rough start can become smoother with time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23] Our previous work found that not all parents of children with cancer experienced supportive relationships with their children's oncology clinicians, with nearly one-quarter of these parents identifying substantial challenges soon after diagnosis. 9 Such relationships can evolve; however, in the best case, a rough start can become smoother with time.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate variables were based on previous findings and reports at baseline, including parent sociodemographic factors and mental health, clinician factors, and health care systems factors, such as care across transitions. 9 A backward variable selection procedure was used to construct the multivariable model, with a significance level of P = .05 for removal from the model. Mixed-effects multinomial logistic regression models were also used to examine the association between strategies used by clinicians to work with parents and patterns of change in challenges over time.…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such she was considering refusal of additional cancer-directed therapies to prevent further developmental regression, a course she believed would be in the interest of her child's overall wellbeing. Children with trauma histories, behavioral challenges, transitions in primary caregivers 14 Help parents to create physical and emotional safety for their child 14 Parent Psycho-education, sessions with parents to conceptualize child's trauma/behaviors, in the moment feedback on child's behaviors and parent responses 14 Higher quality attachment relationships, 6,7 positive impacts on cognitive development, 14 long-term benefits to symptoms of PTSD and reduction of mental health diagnosis 13…”
Section: Family Concernsmentioning
confidence: 99%
“…Moreover, many parents of children with cancer have expressed difficulty in finding their voice and role among their child's care team as well as build strong relationships with physicians. 7 This experience can be further exacerbated by cultural differences and language barriers. As such, mental health services that incorporate parents offer a unique opportunity to leverage the plasticity of the early brain.…”
mentioning
confidence: 99%